PENGARUH PENGGUNAAN APLIKASI BUBYBUS PADA GADGET TERHADAP KEMAMPUAN LITERASI AWAL PADA ANAK KELOMPOK A DI PAUD IT FATHIYYAH - Febriyanti Utami (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aims to determine the effect of BabyBus application on gadgets on early literacy abilities of early childhood in group A in Palembang IT Fathiyyah ECD in 2018. The research method used in this study was an experimental method with posttest only control group design research design. The sampling technique is done by total sampling technique. With a sample of 26 children from groups A1 and A2 in PAUD IT Fathiyyah. Data analysis used is descriptive statistics, inferential statistics and hypothesis testing using the t test. From the results of calculations carried out obtained tcount = 2.268> ttable = 2.064. This means that there are significant differences in early childhood literacy abilities in the A PAUD IT Fathiyyah Palembang group between groups of children who use the application on the gadget in the introduction of letters of the alphabet with groups of children who do not use the BabyBus application in the alphabet letter introduction. From the results of these studies it can be concluded that there is an influence of the use of the BabyBus application on gadgets on early literacy skills in early childhood, especially in the introduction of letters of the alphabet.